Seismic activity studies and seismic risk assessment for some operating dams in Armenia - L. S. Sargsyan (ՀՀ ԳԱԱ հրատ.)
The problem of induced seismicity related with operation of reservoirs is essential in geophysics and earthquake engineering, especially for the reservoirs, which are constructed in seismically active regions. As the whole territory of Armenia is situated in very high seismoactive zone seismic risk assessment of dams is very important task for Armenia. We have collected and analyzed the data on the current reservoir’s and dam’s situation and then pointed out the main factors that determine the risk’s levels. Ջրամբարների շահագործմամբ պայմանավորված հարուցված սեյսմիկությանը, երկրաֆիզիկայի և ինժեներային սեյսմոլոգիայի կա- րևորագույն խնդիրներից է, հատկապես այն ջրամբարների համար, որոնք կառուցված են բարձր սեյսմաակտիվ շրջաններում: Քանի որ Հայաստանի տարածքը գրեթե ամբողջությամբ գտնվում է բարձր սեյսմիկ վտանգի գոտում, պատվարների սեյսմիկ ռիսկի գնահատումը շատ կարևոր խնդիր է: Проблема наведенной сейсмичности, связанной с эксплуатацией водохранилищ, имеет важное значение в геофизике и инженерной сейсмологии, особенно для плотин, которые строятся в сейсмически активных областях. Поскольку вся территория Армении расположена в зоне высокой сейсмоактивности, оценка сейсмического риска плотин является одной из важных задач. Мы собрали и проанализировали данные о текущем состоянии водохранилищ и плотин, а затем указали основные факторы, определяющие уровни риска.
Keywords: Science; Geology; Hydrology; Volcanology